The warmth of our regrets: Managing regret through physiological regulation and consumption1. Issue 2 (2nd September 2016) - Rotman, Jeff D.; Lee, Seung Hwan (Mark); Perkins, Andrew W.
Abstract: This research suggests that experiencing action regret induces a change in psychological and physical warmth, motivating individuals to ameliorate that change via interaction with objects that are perceived to be physically or psychologically opposite in temperature. Experiment 1 revealed individuals experiencing action regret felt more self‐conscious emotions, and subsequently preferred cold (versus hot) drinks. Experiment 2 replicated this effect and ruled out arousal as a possible alternative explanation. Experiment 3 furthered this link by demonstrating that those feeling more self‐conscious emotions felt warmer and subsequently preferred cold (versus hot) drinks. Finally, experiment 4 found that advertisements manipulated for temperature (e.g., cold climate) mitigated the psychological effects of action regret. We interpret the results of these four studies within the emerging field of embodied cognition, which argues that our understanding of emotional concepts is grounded in, and can be influenced by, physical experiences.